Razões de punir: a teoria de H. L. A. Hart - Santos, Paulo Vinícius Borges (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation purpose is to analyze the reasons for punishing from the point of view of the H. L. A. Hart's mixed theory, observing to what extent Hart adopts utilitarian and retributivist theories, especially in Bentham and Kant. For this, one observes the philosophical thought in the conceptualization of the aim of the punishment and the reasons by which one must punish. The purpose is to examine the theories of punishment in order to find answers to the questions: what justifies the general practice of punishment? To whom may punishment be applied? How may we punish? The research is eminently bibliographical, developed from the identification, reading, analysis and interpretation of the writings of the greatest defenders of these philosophical schools. Utilitarianism projects the justification of punishment for the future, aiming at the prevention of new crimes. From another perspective, retributivism, when seeing the penalty as a consequence of crime, returns its view to the past, pointing as its foundation the merit and punishment of the offender. Hart defends for the integration of the two most important theories of philosophical thought, considering the utilitarian theory as to the general justifying aim, and the retributivist as far as distribution is concerned. From the analysis of Hart's mixed theory it is observed that, faced with the complexity of the institute of punishment, the reason for punishing is revealed in a mixed and balanced system, which includes both retribution to the offender for wrongdoing and the prevention of new offenses.
Keywords: Hart; Crime; Punição; Hart; Crime; Punishment; ACCNPQ::Ciências Humanas::Filosofia